On the Existence of a Unique Green Function for the Linear Extension of a Dynamical System on a Torus - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove two theorems on the existence of a unique Green function for a linear extension of a dynamical system on a torus. We also give two examples of the construction of this function in explicit form.